2022
DOI: 10.1111/mbe.12315
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Teachers the Genetics of Learning: An Application of the Mixed Blessings Model

Abstract: Decades of educational genetics research have highlighted that differences in academic achievement are partly explained by genetic variation between individuals. Consequently, there is ongoing discussion about whether genetic influences on educationally related traits should be more widely acknowledged in schools and communicated specifically to teachers. Nonetheless, there is little research on how teachers might interpret such information, and how it might alter their perceptions of the students they teach o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
(148 reference statements)
0
0
0
Order By: Relevance
“…These results suggest that legal professionals see potential benefits in increased understanding of genetic and environmental influences on educational processes. However, recent research has demonstrated that partial knowledge may be a mixed-blessing in education (Larsen et al 2022). Much work is needed to understand how gene-environment information can be brought to educators, parents and students in the most beneficial way.…”
Section: Can Our Understanding Of How Genes Influence Academic Achiev...mentioning
confidence: 99%
“…These results suggest that legal professionals see potential benefits in increased understanding of genetic and environmental influences on educational processes. However, recent research has demonstrated that partial knowledge may be a mixed-blessing in education (Larsen et al 2022). Much work is needed to understand how gene-environment information can be brought to educators, parents and students in the most beneficial way.…”
Section: Can Our Understanding Of How Genes Influence Academic Achiev...mentioning
confidence: 99%